No pain no gain: reflections on the promises and challenges of embedding reflective practices in large classes. Issue 5 (3rd September 2019) - Korucu Kis, Saadet; Kartal, Galip
ABSTRACT: Reflective teaching is considered as the optimal approach to teacher education and it is suggested to be taught before the practicum starts. However, there is a lack of research investigating whether large classes constitute an obstacle to the implementation of reflective practices in teacher education programs. Engaging 60 third-year English as a foreign language (EFL) student teachers in reflective practices through the procedures of self-monitoring, peer-observation, and journal writing in a campus-based course, this study aimed to find out what benefits and problems student teachers would experience throughout the process. Participants acknowledged that involvement in reflective practices helped them develop self-awareness, criticality and reflective mindsets while also expanding understanding of new content. They also indicated three major challenges in observing self and peers, and writing journals: lack of reflective skills, time pressure, and repetitive process. The researchers conclude that implementing reflective practices is demanding but attainable in large classes.